Fetal Outcomes of Preeclampsia (Medical Forum Monthly, 2020)
Objective: To evaluate different factors which effect preeclampsiaand fetal outcomes in this condition.Study Design: Case control studyPlace and Duration of Study: This study was conducted at the Holy Family Hospital and Rawalpindi General Hospital Islamabad from January 2017 to November 2019.Materials and Methods: One hundred and sixty pregnant women were included. Out of those, 110 were preeclamptic who developed hypertension and protein urea after 20th week of gestation. The remaining fifty pregnant women who had normal blood pressure during the whole tenure of their pregnancy were taken as the control group.Results: Majority (40.9%) of cases, who developed preeclampsia were younger (16-20 year) women, and this frequency gradually decreased with advancing age. Only (18.14%)of pregnant women beyond 31-35+ years of age developed preeclampsia. Moreover, weight of baby at the time of delivery was significantly lower among cases as compared to controls. In the present study there were 89% live births, 10% still births due to growth retardation and 1% cases of still birth due to fetal distress in preeclamptic patients. As a consequence of severe hypertension during pregnancy, a maximum number of still births (22.2%) were observed in primigravida patients of age group16-20 which were due to growth retardation.Conclusion: Preeclampsia is a worsening clinical condition and if not monitored carefully may result in complications of pregnancy, thus affecting the baby.